Multi-objective DG placement in radial distribution systems using the IbI logic algorithm - Saxena, Nitin; Pandit, M; Srivastava, L (Frontiers in Energy Research, 2024)
This paper presents a unique optimization method based on the incomprehensible but intelligible-in-time (IbI) logic algorithm (ILA) to optimally place dispersed generators in small, medium, large, and very large (16-, 33-, 69-, and 118-bus) radial distribution power networks to reduce power losses, the total operating cost, and the voltage deviation and improve the voltage level. Two types of multiple distributed generators (DGs) are employed in this study, one working at unity power factor and the other at 0.866 p.f. The IbI logic algorithm works by understanding concepts that are not currently recognized as logical but are expected to become logical over time. The proposed approach was used to address a multi-objective multi-DG placement problem. The results generated through this method were compared with those generated by other methods and were observed to be comparatively remarkable.